Studi eksploratif pengembangan design kegiatan PPL-KKN integratif Fakultas Tarbiyah dan Keguruan - Karwadi, Karwadi; Nugraheni, Aninditya Sri; Lestari, Shindy (Ta'dibuna: Jurnal Pendidikan Islam, 2021)
The purpose of this study describes PPL-KKN activities obtained by students including teaching exercises and educational tasks in a guided and integrated manner for the formation of the profession. The study uses descriptive and critically-analytical methods with inductive thinking techniques. Data collection technique is field research (field research) which amounted to 49 schools / madrasas. Research data is collected through interview methods with school/madrassa representative research subjects. The results of this study show that: 1) The school / madrasah gave a positive response to the integrative PPL-KKN activities. 2) The interests, expectations, abilities, and policies of PPL-KKN activities are considered to be in accordance with the interests of schools / madrassas, but there must be socialization, DPL communication with the school, relevant student work programs, and adequate student soft-skill skills. 3) PPL-KKN activities development steps carry out socialization activities, student debriefing activities in small groups with the main materials of student soft-skill development and the ability to structure work programs. So it is very important to develop the design of PPL-KKN Integrative there is a link and match between education and the job market. Abstrak Tujuan Penelitian ini mendeskripsikan kegiatan PPL-KKN yang diperoleh oleh mahasiswa mencakup latihan mengajar serta tugas kependidikan secara terbimbing dan terpadu untuk pembentukan profesi. Penelitian ini menggunakan metode deskriptif dan kritis-analitis dengan teknik berpikir induktif. Teknik pengumpulan data adalah penelitian lapangan (field research) yang berjumlah 49 sekolah/madrasah. Data penelitian dikumpulan melalui metode wawancara dengan subjek penelitian perwakilan sekolah/madrasah. Hasil penelitian ini menunjukkan bahwa: 1) pihak sekolah/madrasah memberikan tanggapan positif terhadap kegiatan PPL-KKN Integratif. 2) Sisi minat, harapan, kemampuan, dan kebijakan kegiatan PPL-KKN dipandang telah sesuai dengan kepentingan sekolah/madrasah, namun harus adanya sosialisasi, komunikasi DPL dengan pihak sekolah, program kerja mahasiswa yang relevan, serta kemampuan soft-skill mahasiswa yang memadai. 3) Langkah-langkah pengembangan kegiatan PPL-KKN melaksanakan kegiatan sosialisasi, kegiatan pembekalan mahasiswa dalam kelompok kecil dengan materi pokok pengembangan soft-skill mahasiswa dan kemampuan menyusun program kerja. Sehingga sangat penting pengembangan desain PPL-KKN Integratif terdapat adanya link and match antara pendidikan dengan pasar kerja.